2017
DOI: 10.4049/jimmunol.1601975
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Signaling Contributes to Sex Differences in Macrophage Polarization during Asthma

Abstract: Allergic asthma is a chronic Th2 inflammation in the lungs that constricts the airways and presents as coughing and wheezing. Asthma mostly affects boys in childhood and women in adulthood, suggesting that shifts in sex hormones alter the course of the disease. Alveolar macrophages have emerged as major mediators of allergic lung inflammation in animal models as well as humans. Whether sex differences exist in macrophage polarization and the molecular mechanism(s) which drive differential responses are not wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 83 publications
11
97
0
6
Order By: Relevance
“…While studies in cells and animal models have addressed the contributions of male and female sex hormones to lung immunity (Keselman and Heller ; Keselman et al. ; Fuseini et al. ), only a few studies have addressed the mechanisms by which physiological hormonal fluctuations that occur in the female reproductive cycle affect the inflammatory response (Fuentes et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies in cells and animal models have addressed the contributions of male and female sex hormones to lung immunity (Keselman and Heller ; Keselman et al. ; Fuseini et al. ), only a few studies have addressed the mechanisms by which physiological hormonal fluctuations that occur in the female reproductive cycle affect the inflammatory response (Fuentes et al.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies in cells and animal models have also shown that sex hormones can affect airway tone, inflammation, immune cell function, and transcription of specific genes that alter host immunity and promote immune cell proliferation (Chang and Mitzner 2007;Fuseini and Newcomb 2017;Yung et al 2018). While studies in cells and animal models have addressed the contributions of male and female sex hormones to lung immunity (Keselman and Heller 2015;Keselman et al 2017;Fuseini et al 2018), only a few studies have addressed the mechanisms by which physiological hormonal fluctuations that occur in the female reproductive cycle affect the inflammatory response Fuentes and Silveyra 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with female subjects, postmenarche, having a more T H 2-biased immune system, making them prone to allergy. 54 However, after 3 years of VIT, the female subjects in both groups had reduced specific IgE levels, indicating that VIT is effective irrespective of sex.…”
Section: Discussionmentioning
confidence: 90%
“…Several experimental models have reported a host of immunological effects of E2 including a role in DC maturation, effects on CD103 + DC and macrophage polarization in the airways. Some of these effects are directly mediated through estrogen receptors that are expressed widely across cell populations in the immune system.…”
Section: Discussionmentioning
confidence: 99%